Brackish to freshwater dinoflagellate cyst assemblages from the La Colonia Formation (Paleocene?), Northeastern Patagonia, Argentina. - Guler, Maria Veronica (2014)
The palynological analysis of the La Colonia Formation at the San Miguel section yielded conspicuous organic-walled dinoflagellate cyst (dinocyst) and green algae assemblages. The presence of a monotypic palaeoperidinioid dinocyst assemblage of Ginginodinium/Laciniadinium sp. in the basal levels of this section indicates low-salinity water conditions in a restricted shallow marine palaeoenvironment. Green algae-dominated assemblages together with specimens of Morkallacysta spp., Dinocysts type P and ?Vesperopsis sp. recorded in the middle and upper part of the San Miguel section indicate brackish to freshwater and freshwater depositional conditions, respectively. The changes in the composition of the palynological assemblages, in agreement with the analysis of the sedimentary facies, reflect a decrease in the salinity of the water bodies and a progressive shallowing upward trend. The occurrence of neritic open marine specimens of Cribroperidinium spp., Apteodinium sp., Circulodinium sp. and Areoligera sp. cf. A. gippingensis Jolley is here considered as reflecting contemporaneous transported material from the adjacent platform. Biostratigraphical control provided by palynomorphs suggest an age no older than Paleocene for these deposits of the La Colonia Formation.